Overview of TFAST and AFAST: point‐of‐care ultrasounds and how to perform them. Issue 9 (4th November 2022) - Lewis, Dan; Bassolino, Serena
Abstract : Background : Assessment of emergency patients can be fraught with difficulty. The adoption of certain, straightforward ultrasound techniques can add vital information to assist veterinary surgeons with both initial triage and disease progression. Aim of the article : This article aims to provide an introductory guide to performing point‐of‐care ultrasound for veterinary practitioners, as well as detailing some of the diagnostic information that can be obtained.